Surface Enamel Remineralization: Biomimetic Apatite Nanocrystals and Fluoride Ions Different Effects. (5th April 2009) - Roveri, Norberto; Battistella, Elisa; Bianchi, Claudia Letizia; Foltran, Ismaela; Foresti, Elisabetta; Iafisco, Michele; Lelli, Marco; Naldoni, Alberto; Palazzo, Barbara; Rimondini, Lia
Abstract : A new method for altered enamel surface remineralization has been proposed. To this aim carbonate-hydroxyapatite nanocrystals which mimic for composition, structure, nanodimensions, and morphology dentine apatite crystals and resemble closely natural apatite chemical-physical properties have been used. The results underline the differences induced by the use of fluoride ions and hydroxyapatite nanocrystals in contrasting the mechanical abrasions and acid attacks to which tooth enamel is exposed. Fluoride ions generate a surface modification of the natural enamel apatite crystals increasing their crystallinity degree and relative mechanical and acid resistance. On the other hand, the remineralization produced by carbonate-hydroxyapatite consists in a deposition of a new apatitic mineral into the eroded enamel surface scratches. A new biomimetic mineral coating, which progressively fills and shadows surface scratches, covers and safeguards the enamel structure by contrasting the acid and bacteria attacks.